Application of Multimedia Interactive Learning Based on Problem-Based Learning to Improve Students' Cognitive Learning Outcomes and Critical Thinking Skills - Ananti, Yoananda Ramadina; Anggraini, Atika (Islamic Journal of Integrated Science Education (IJISE), 2023)
The purpose of the study is to determine how applying multimedia interactive learning based on problem-based learning affects students in the XI IPA grade at Senior High School’s cognitive learning outcomes and critical thinking skills. Purposive sampling and a nonrandomized control group pretest-posttest design are employed in this quasi-experimental study design. Students from class XI IPA 5 (the experimental class) and class XI IPA 6 (the control class) were the samples used; each was assigned a pretest and a posttest. The study's instruments comprise non-tests such as observation sheets for syntax execution, double-choice tests for cognitive learning outcomes, and essays for critical thinking skills. The treatment instruments include learning gadgets and measurement instruments. The findings of the cognitive learning exam yielded an Fcount of 18,375 with a p-value of 0.000 < α (α = 0.05) when analyzed, whereas the results of the critical thinking skills test yielded an Fcount of 18,648 with a p-value of 0.000 < α (α = 0.05). The test results of the hypothesis showed that H0 was rejected and the research hypotheses were accepted. In order to draw the conclusion that the application of multimedia interactive learning based on problem-based learning improved the cognitive learning outcomes and critical thinking skills of eleventh grade students at Senior High School.